PENDAMPINGAN PERBANYAKAN TRICHODERMA SP SEBAGAI BIOPESTISIDA MENGGUNAKAN MEDIA JAGUNG DI LABORATORIUM LAPANGAN SIKKA - Dalia, Maria Stefania; Yovita Yasintha Bolly; Mario Malado (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
This research aims to find out how the manufacturing process is Trichoderma sp by using corn media in the Laboratory. The use of Trichoderma sp. by using corn media which is considered more environmentally friendly, cheap and easy to obtain so that it attracts the attention of employees of the East Flores Regency Plantation Office, as one of the options and solutions in controlling pests and diseases in plants using corn media. To Collection This data, the author uses the observation method. Meanwhile, secondary data is usually stored in documents that have become archives. Data sources are usually obtained from journals, past reports, company websites and other sources. The location of the internship activity was carried out at the Sikka Field Laboratory (LL) located in Uneng City Village, Alok District, Sikka Regency, NTT. From the results of making Trichoderma sp. By using this corn medium, the best results of the growth of Trichoderma sp. By using corn media on the 7th day after the manufacturing process, the growth is already good. After 14 days of growth of Trichoderma sp. can be harvested and applied to all types of plants. Therefore, based on the results of this study, it can generally be said that corn is the most effective medium to be used as a propagation medium for Trichoderma sp. From the results carried out, it can be recommended that to control pests and diseases on plants, it is better to use Trichoderma sp. Trichoderma sp. also functions as a decomposer, and also as a biological agent of plant growth.